The effect of formalizing enhanced recovery after esophagectomy with a protocol. Issue 6 (18th May 2014) - Findlay, J. M.; Tustian, E.; Millo, J.; Klucniks, A.; Sgromo, B.; Marshall, R. E. K.; Gillies, R. S.; Middleton, M. R.; Maynard, N. D.
Summary Enhanced recovery after surgery (ERAS) pathways aim to accelerate functional return and discharge from hospital. They have proven effective in many forms of surgery, most notably colorectal. However, experience in esophagectomy has been limited. A recent study reported significant reductions in pulmonary complications, mortality, and length of stay following the introduction of an ERAS protocol alone, without the introduction of any clinical changes. We instituted a similar change 16 months ago, introducing a protocol to provide a formal framework, for our existing postoperative care. This retrospective analysis compared outcome following esophagectomy for the 16 months before and 20 months after this change. Data were collected from prospectively maintained secure web‐based multidisciplinary databases. Complication severity was classified using the Clavien‐Dindo scale. Operative mortality was defined as death within 30 days of surgery, or at any point during the same hospital admission. Lower respiratory tract infection was defined as clinical evidence of infection, with or without radiological signs. Respiratory complications included lower respiratory tract infection, pleural effusion (irrespective of drainage), pulmonary collapse, and pneumothorax. Statistical analysis was performed using SPSS v21. One hundred thirty‐two patients underwent esophagectomy (55 protocol group; 77 before). All were performed open. There were no differences between the two groups in terms of age, gender, operation, use of neoadjuvant therapy, cell type, stage, tumor site, or American Society of Anesthesiologists grade. Median length of stay was 14.0 days (protocol) compared with 12.0 before (interquartile range 9–19 and 9.5–15.5, respectively; P = 0.073, Mann–Whitney U‐test). Readmission within 30 days of discharge occurred in five (9.26%) and six (8.19%; P = 1.000, Fisher's exact test). There were four in‐hospital deaths (3.03%): one (1.82%) and three (3.90%), respectively (P = 0.641). There were no differences in the severity of complications (P = non‐significant; Pearson's chi‐squared). There were no differences in the type of complications occurring in either group. The protocol was completed successfully by 26 (47.3%). No baseline factors were predictive of this. In contrast to previous studies, we did not demonstrate any improvement in outcome by formalizing our existing pathway using a written protocol. Consequently, improvements in short‐term outcome from esophagectomy within ERAS would seem to be primarily due to improvements in components of perioperative care. Consequently, we would recommend that centers introducing new (or reviewing existing) ERAS pathways for esophagectomy focus on optimizing clinical aspects of such standardized pathways.